ANALISIS PRODUKTIVITAS TENAGA KERJA DITINJAU DARI IDLE TIME PADA PEKERJAAN STRUKTUR ATAS PROYEK KONSTRUKSI GEDUNG HEALTH SCIENCE UNIVERSITAS AIRLANGGA - Daffa Hadyanata Putra; Krisna Dwi Handayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Labor productivity is one aspect that can determine the success of a construction project. This study aims to analyze labor productivity in terms of idle time and identify the contributing factors in the Airlangga University Health Science Building Construction Project. Data collection was conducted using continuous observation methods, a labor perception questionnaire, and in-depth interviews with project structural staff. Identification of the contributing factors to idle time was conducted using a data integration approach, a fishbone diagram, and a 5 Whys analysis to explore the root cause. The results of the study showed that the actual productivity of labor in column reinforcement work was 2,60 kg/person-hour, beam reinforcement was 5,80 kg/person-hour, plate reinforcement was 2,65 kg/person-hour, column formwork was 2,39 m²/person-hour, beam formwork was 0,30 m²/person-hour, plate formwork was 0,67 m²/person-hour, column casting was 0,66 m³/person-hour, and beam and plate casting was 0,18 m³/person-hour. Overall, the labor had a productive time of 68.29% and idle time of 31.71%, which is categorized as